A probabilistic prediction model for the corrosion initiation time of steel reinforcement in concrete structures. (1st January 2011) - Li, Linyuan; Damrongwiriyanupap, Nattapong; Xi, Yunping
This paper presents an analytic method for predicting the probabilistic features of corrosion initiation time of reinforcement in concrete structures subjected to chloride environments. By using the analytic solution of non-linear chloride diffusion equation, and using statistic data for thickness of concrete cover, water-to-cement ratio, curing time, chloride diffusion coefficient, surface chloride concentration and chloride threshold value, both the mean and standard deviation of the corrosion initiation time can be calculated analytically.